Loss of primary cilia promotes mitochondria-dependent apoptosis in thyroid cancer - Lee Junguee; Park Ki Cheol; Sul Hae Joung; Hong Hyun Joung; Kim Kun-Ho; Kero Jukka; Shong Minho (NATURE RESEARCH, 2025)
The primary cilium is well-preserved in human differentiated thyroid cancers such as papillary and follicular carcinoma. Specific thyroid cancers such as Hurthle cell carcinoma, oncocytic variant of papillary thyroid carcinoma (PTC), and PTC with Hashimoto's thyroiditis show reduced biogenesis of primary cilia; these cancers are often associated the abnormalities in mitochondrial function. Here, we examined the association between primary cilia and the mitochondria-dependent apoptosis pathway. Tg-Cre;Ift88(flox/flox) mice (in which thyroid follicles lacked primary cilia) showed irregularly dilated follicles and increased apoptosis of thyrocytes. Defective ciliogenesis caused by deleting the IFT88 and KIF3A genes from thyroid cancer cell lines increased VDAC1 oligomerization following VDAC1 overexpression, thereby facilitating upregulation of mitochondria-dependent apoptosis. Furthermore, VDAC1 localized with the basal bodies of primary cilia in thyroid cancer cells. These results demonstrate that loss-of-function of primary cilia results in apoptogenic stimuli, which are responsible for mitochondrial-dependent apoptotic cell death in differentiated thyroid cancers. Therefore, regulating primary ciliogenesis might be a therapeutic approach to targeting differentiated thyroid cancers.